حملات مقاطعة المنتجات الاسرائيلية وانعكاسها على اتجاهات المستهلك الفلسطيني نحو المنتجات الفلسطينية: (مدينة بيتونيا حالة دراسية) - د. سامي أحمد عيدة (Zenodo, 2019)
حملات مقاطعة المنتجات الاسرائيلية وانعكاسها على اتجاهات المستهلك الفلسطيني نحو المنتجات الفلسطينية: (مدينة بيتونيا حالة دراسية) د. سامي أحمد عيدة Boycott Campaigns Against the Israeli Products and their Impact on the Attitudes of the Palestinian Consumers towards the Palestinian Products: Beitunia as a Case Study Dr. Sami Ahmad Eideh ملخص: هدفت الدراسة التعرف إلى معرفة انعكاس حملات مقاطعة المنتجات الإسرائيلية على اتجاهات المستهلك الفلسطيني نحو المنتجات الفلسطينية. وذلك من خلال معرفة مدى وعي المستهلك لمفهوم مقاطعة المنتجات الإسرائيلية، ومدى استجابته لحملات المقاطعة. وكذلك التعرف إلى اتجاهات المستهلكين الفلسطينيين نحو المنتجات الوطنية ومقاطعة المنتجات الإسرائيلية، والتعرف إلى الوسائل التي يجب اتباعها حتى يرتقي المنتج المحلي إلى المستوى المطلوب من وجهة نظر المستهلك الفلسطيني. وقد استخدم الباحث المنهج الوصفي التحليلي، كما قام بتصميم استبانة خصيصا لهذا الغرض تتكون من ستة محاور، حيث اعتمدت الدراسة على عينة عشوائية قوامها (60) استبانة استعيد منها (56) استبانة. وتم تحليل إجابات المستهلكين وتفسيرها للوصول إلى إجابات للتساؤلات والفرضيات التي وضعها الباحث باستخدام برنامج التحليل الإحصائي (spss) كرزمة إحصائية لإدخال البيانات ومعالجتها واختبار الفرضيات، ومن أهم النتائج التي توصل إليها الباحث: أن حملات المقاطعة لم تنعكس إيجاباً على اتجاهات المستهلك نحو المنتج المحلي الفلسطيني، وبالتالي هناك قصور لدى المنتج الفلسطيني في استغلال الفرصة التي أتيحت له لإحلال جزء كبير من السلع الوطنية محل السلع الإسرائيلية. ومن أهم توصيات الدراسة: ضرورة تطوير المنتجات المحلية، وفرض قيود رقابية عليها ضمن معايير الجودة والمواصفات، وذلك لتسهيل عملية إحلالها محل المنتجات الإسرائيلية، والتركيز في عملية الترويج والتسويق على مواصفات المنتج الجيدة، والسعي لزيادة الوعي الوطني لدى المستهلك الفلسطيني بأهمية استهلاك المنتجات المحلية ومقاطعة المنتجات الإسرائيلية. Abstract: This study aimed at investigating the impact of boycott campaigns against the Israeli products on Palestinians attitudes towards domestic products. The study also attempted to explore the consumer’s conception and awareness towards boycotting the Israeli products and the level of their response to it. Furthermore, the study sought to analyze the Palestinian consumers’ attitudes towards local products and the boycott of Israeli ones. In addition, the researcher aimed at exploring the means that should be followed to promote domestic products from the perspective of the Palestinian consumer. To achieve the study’s objectives, the researcher used the descriptive analytical approach through developing a questionnaire that consisted of six domains. The study included a random sample that consisted of 60 persons. Out of the 60 questionnaire, 56 were retrieved. The consumers’ responses were analyzed and interpreted using SPSS software. The study yielded various results, yet the most important of which is that the boycott campaigns did not positively influence the consumers’ attitudes towards domestic products, which indicates a failure on the part of Palestinian producer to exploit the opportunity to substitute Israeli products with Palestinian ones. The study also resulted in a number of recommendations such as, the need for developing the domestic products, the need for imposing control and regulations over the local products to ensure their quality and high specifications in order to facilitate the substitute of the Israeli products, the need for focusing on the good features of the local products in marketing, and finally the need for increasing the awareness of the Palestinian consumer on the importance of consuming domestic products and boycotting Israeli ones. Keywords: Boycott Campaigns Against the Israeli Products Palestinian Products; Attitudes of Palestinian Consumers.